Crossing the river by touching the stones alternative approaches in Technical and Vocational Education and Training in the People’s Republic of China and the Republic of Korea - Asian Development Bank (Manila,Philippines Asian Development Bank, 2021)
It also presents TVET systems in Germany and the United Kingdom to illustrate the diverse paths in developing such systems. This publication reconfirms that there is no "one-size-fits-all" for TVET. The good practices in Asia are expected to inspire policymakers to explore different TVET models and come up with new ways of delivery that best suit their own country context.
Executive Summary - - Model of Technical and Vocational Education and Training in the World - - Experience of the Republic of Korea - - Experience of the People’s Republic of China - - Conclusion.
Keywords: Vocational education -- China; Vocational education -- Korea; Technical education -- Economic aspects -- China; Technical education -- Economic aspects -- Korea